International students’ fear of crime: an Australian case study - Xiong, Lin (The Australian and New Zealand journal of criminology, 2017)
Concerns about safety and fear of being victimised by crime have become important factors determining international students’ decisions of where to study. Host governments and educational agencies have introduced a range of programs to ease such concerns. However, these recommendations are seldom informed by the criminology literature on fear of crime and the effectiveness of most of these practices has been rarely tested. Drawing upon a survey on 610 international students studying in Melbourne, Australia, during the period of 2009 and 2010, this paper finds that an overwhelming majority of international students have experienced racially oriented victimisation and have feared that they may be victimised because of their ethnic origin. Opportunities for socialization help international students feel safe about an environment, but it also increases their levels of fear of crime. Perceived social disorder makes international students feel unsafe and heightens their levels of fear of being victimised. Findings provide important implications for a range of stakeholders in countries that host international students.